Isolated nociceptors reveal multiple specializations for generating irregular ongoing activity associated with ongoing pain. Issue 11 (November 2018) - Odem, Max A.; Bavencoffe, Alexis G.; Cassidy, Ryan M.; Lopez, Elia R.; Tian, Jinbin; Dessauer, Carmen W.; Walters, Edgar T.
Abstract : Abstract: Ongoing pain has been linked to ongoing activity (OA) in human C-fiber nociceptors, but rodent models of pain-related OA have concentrated on allodynia rather than ongoing pain, and on OA generated in non-nociceptive Aβ fibers rather than C-fiber nociceptors. Little is known about how ongoing pain or nociceptor OA is generated. To define neurophysiological alterations underlying nociceptor OA, we have used isolated dorsal root ganglion neurons that continue to generate OA after removal from animals displaying ongoing pain. We subclassify OA as either spontaneous activity generated solely by alterations intrinsic to the active neuron or as extrinsically driven OA. Both types of OA were implicated previously in nociceptors in vivo and after isolation following spinal cord injury, which produces chronic ongoing pain. Using novel automated algorithms to analyze irregular changes in membrane potential, we have found, in a distinctive, nonaccommodating type of probable nociceptor, induction by spinal cord injury of 3 alterations that promote OA: (1) prolonged depolarization of resting membrane potential, (2) a hyperpolarizing shift in the voltage threshold for action potential generation, and (3) an increase in the incidence of large depolarizing spontaneous fluctuations (DSFs). Can DSFs also be enhanced acutely to promote OA in neurons from uninjured animals? A low dose of serotonin failed to change resting membrane potential but lowered action potential threshold. When combined with artificial depolarization to model inflammation, serotonin also strongly potentiated DSFs and OA. These findings reveal nociceptor specializations for generating OA that may promote ongoing pain in chronic and acute conditions. Abstract : Supplemental Digital Content is Available in the Text.Neurophysiological specializations for generating ongoing electrical activity likely to promote ongoing pain have been defined in isolated primary nociceptors in neuropathic and inflammatory pain models.